The Influence of Social Media Marketing, Brand Equity, and Social Brand Engagement on Repurchase Intention Toward NPURE Skincare Brand - Pratiwi, Laras Bunga; Rizan, Mohamad; Krissanya, Nofriska (LPPPIPublishing, 2025)
This study aims to determine the effect of social media marketing, brand equity, and social brand engagement on repurchase intention on the NPURE skincare brand. The research method used in this research is quantitative method by distributing questionnaires. Sampling using purposive sampling technique by obtaining 302 respondents as samples. The population in this study consists of individuals who have used NPURE skincare products and follow the Instagram account @npureofficial. This research was processed using SPSS version 25.0 software and SEM (Structural Equation Model) through AMOS to analyze and generate data from this research. The result of this study indicate that First, social media marketing have a positive and significant influence on brand equity, social brand engagement, and repurchase intention. Second, brand equity and social brand engagement have a positive and significant influence on repurchase intention.